Sociodemographic determinants of maternal knowledge, attitude and uptake of routine immunization in ‘Sabo’ and ‘Non-Sabo’ communities in Awka, Nigeria - Nnebue, Chinomnso C.; Anaekwe, Chidebe O.; Anaekwe, Adaeze N. (International Journal of Advances in Medicine, 2018)
Background: Routine immunization coverage has been reportedly hampered by migration, and user characteristics, such as maternal knowledge and attitude. An understanding of these maternal variables could help modify preventive strategies. The objective of the present study was to assess and compare the Sabo and non-Sabo communities in Awka, Nigeria for sociodemographic determinants of maternal knowledge, attitude and uptake of routine immunization Methods: A community based comparative study of 420 mothers and caregivers in Awka selected via multistage sampling technique, was conducted between July and October 2015. Data collection was by interview using semi-structured questionnaire, while analysis was done with Statistical Package for Social Sciences version 22.0. Chi-square, Fisher’s exact, Yates correction and student’s t tests were used to determine statistically significant associations between variables at p value of < 0.05. Results: There was normal distribution of age groups of respondents for both communities. Married women (53.0%) in Sabo communities had better knowledge of routine immunization than (47.0%) in non-Sabo communities (p= 0.000). Self-employed women were the most knowledgeable in routine immunization 310 (74.0%) (p= 0.042). Married women in the Sabo communities (53.0%) had better attitude than (47.0%) (p= 0.000).in non-Sabo communities. The maternal uptake of routine immunization among the different communities, ethnic and religious groups were higher in non-Sabo, Igbo/others and Christian groups than the Sabo, Hausa/Fulani and Muslim groups. (p= 0.010). Conclusions: This study found differences in baseline socio-demographic characteristics of the two communities, as well as better knowledge, attitude and uptake of routine immunization among the non-Sabo (Ibo/others and Christians) than the Sabo (Hausa/Fulani and Muslims). Addressing issues of factors identified to affect routine immunization will greatly assist in boosting uptake of routine immunization in both communities.